The formulation of competitive actions in practice - Shaw, Richard (Cranfield University, 2016)
This is a study of what managers do in relation to the formulation of competitive actions. The study started with Project 1 (P1), a literature review that looked at managers’ cognitions in respect of competitive positioning and competitive strategy. A gap was found in how individual competitive actions are formulated and executed. A gap was also found concerning what managers do in response to interpretations of their competitive environments. Following the literature review, a series of semi-structured interviews were undertaken with managers and 26 individual competitive actions were recorded and analysed in Project 2 (P2). A structure to the formulation of competitive actions was discerned and developed into a processual model that is triggered by a stimulus, followed by the manager envisaging desired outcome and setting objectives, then deciding which levers to use, developing the action and refining it. Its application to practice was developed in Project 3 (P3) through an aide memoir tool to assist managers. The study makes a contribution to theory by providing a framework that captures the way in which managers construe and formulate competitive actions. In P2 it was found that managers tend to follow a largely homogenous process and that the tools and techniques offered in the extant literature are seldom used. The managers interviewed in mature industries were far more aware of who their competitors were in more when compared to nascent industries. This had a bearing on the formulation of competitive actions insofar as companies operating in mature industries formulated competitive actions to fend off or compete with their competitors more effectively while companies operating in nascent industries tended to formulate competitive actions with the aim of exploiting gaps in the market. It was found in P2 that managers’ backgrounds, including their functional and educational, as well as their nationalistic and cultural backgrounds, had a bearing on how they construed their competitors and the competitive actions they formulated. It was also found that competitive actions were formulated and executed on an iterative process, whereby managers would refine their actions applying the learnings from previous actions. Managers, particularly those with more experience, relied heavily on intuition and tacit knowledge, as well as input from colleagues and customers, when formulating competitive actions. Contrary to the assertions many in much of the extant literature about companies not deviating from industry norms when formulating competitive actions, the study found that managers would often do so in search of abnormal profits. The study makes a contribution to practice by providing a guide to assist in formulating competitive actions. The guide is based on the processual model developed in P2 and was summarised in five key steps, comprising Stimulus, Objectives, Levers, Actions and Refinement, and abbreviated ‘SOLAR’.